Cellular Glass Manufactured by Microwave Irradiation of Residual Glass, Eggshell and Borax - Lucian Paunescu; Sorin Mircea Axinte; Felicia Cosmulescu (Journal La Multiapp, 2021)
The paper presents an improved method of manufacturing cellular glass using residual glass (91 %), sodium borate (5 %), eggshell waste (4 %) and added water (9 %). Compared to methods using eggshell as an expanding agent producing cellular glass with low compression strength, the technique adopted by the authors is original by the addition of sodium borate, which contributes to increasing the compression strength and the use of the unconventional electromagnetic wave heating method, which ensures very economical specific energy consumption. The optimal variant of cellular glass had the following characteristics: density of 0.40 g/cm3, porosity of 81 %, heat conductivity of 0.086 W/m·K, compression strength of 4.3 MPa and the cell dimension between 0.3-0.9 mm. The specific energy consumption of the process was 0.80 kWh/kg. The product has adequate features for using as a heat insulation material under conditions of quite high mechanical loading.